A flexible solid-state zinc ion hybrid supercapacitor based on co-polymer derived hollow carbon spheres. Issue 13 (14th March 2019) - Chen, Shengmei; Ma, Longtao; Zhang, Kui; Kamruzzaman, M.; Zhi, Chunyi; Zapien, Juan Antonio
Abstract : For the first time solid-state zinc ion hybrid supercapacitors based on co-polymer derived hollow carbon spheres with good flexibility have been developed. Abstract : High electrochemical performance energy storage devices coupled with low cost and high safety operation are in urgent need due to the increasing demand for flexible and wearable electronics. For these applications lithium-ion and sodium-ion batteries are vastly limited due to their relatively low power density and security risks. On the other hand, conventional supercapacitors are suitable for flexible and wearable electronics due to their high power density while their low energy density has hindered their wide applications. Lithium or sodium ion hybrid supercapacitors are promising energy storage devices that benefit from the combined high energy density of batteries and high power density of supercapacitors. However, the use of organic electrolytes and shortage of lithium resources are expected to limit their widespread commercialization for flexible and wearable electronics. Here, for the first time, we introduce a safe and flexible solid-state zinc ion hybrid supercapacitor (ZHS) based on co-polymer derived hollow carbon spheres (HCSs) as the cathode, polyacrylamide (PAM) hydrogel as the electrolyte and Zn deposited on carbon cloth as the anode. Owing to the high surface area of the HCSs and the hollow structure which improves the ion adsorption and desorption kinetics of the cathode, the flexible solid-state ZHS delivers a highest capacity of 86.8 mA h g −1 and a maximum energy density of 59.7 W h kg −1 with a power density of 447.8 W kg −1 . Besides, it displays excellent cycling stability with 98% capacity retention over 15 000 cycles at a current density of 1.0 A g −1 . Moreover, the solid-state ZHS is flexible enough to sustain various deformations including squeezing, twisting and folding due to the use of flexible electrodes and electrolytes. Our study unveils a pioneering flexible solid-state ZHS with high safety, which is a promising candidate for flexible and wearable energy storage devices.